GFAPβ and GFAPδ Isoforms Expression in Mesenchymal Stem Cells, MSCs Differentiated Towards Schwann-like, and Olfactory Ensheathing Cells - Nidia Jannette Carrillo González; Gabriela Stefania Reyes Gutierrez; Tania Campos-Ordoñez; Rubén D. Castro-Torres; Carlos Beas Zárate; Graciela Gudiño-Cabrera (Current Issues in Molecular Biology, 2025)
Olfactory ensheathing cells (OECs) and mesenchymal stem cells (MSCs) differentiated towards Schwann-like have plasticity properties. These cells express the Glial fibrillary acidic protein (GFAP), a type of cytoskeletal protein that significantly regulates many cellular functions, including those that promote cellular plasticity needed for regeneration. However, the expression of GFAP isoforms (α, β, and δ) in these cells has not been characterized. We evaluated GFAP isoforms (α, β, and δ) expression by Polymerase Chain Reaction (PCR) assay in three conditions: (1) OECs, (2) cells exposed to OECs-conditioned medium and differentiated to Schwann-like cells (dBM-MSCs), and (3) MSC cell culture from rat bone marrow undifferentiated (uBM-MSCs). First, the characterization phenotyping was verified by morphology and immunocytochemistry, using p75, CD90, and GFAP antibodies. Then, we found the expression of GFAP isoforms (α, β, and δ) in the three conditions; the expression of the GFAPα (10.95%AUC) and GFAPβ (9.17%AUC) isoforms was predominantly in OECs, followed by dBM-MSCs (α: 3.99%AUC, β: 5.66%AUC) and uBM-MSCs (α: 2.47%AUC, β: 2.97%AUC). GFAPδ isoform has a similar expression in the three groups (OEC: 9.21%AUC, dBM-MSCs: 11.10%AUC, uBM-MSCs: 9.21%AUC). These findings suggest that expression of different GFAPδ and GFAPβ isoforms may regulate cellular plasticity properties, potentially contributing to tissue remodeling processes by OECs, dBM-MSCs, and uBM-MSCs.